1999
DOI: 10.1148/radiology.212.3.r99au21896
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Resistance: Noninvasive Measurement with Indexes of Pulmonary Flow Estimated at Velocity-encoded MR Imaging—Preliminary Experience

Abstract: Cardiac output and pulmonary vascular resistance (PVR) were measured in 19 patients by means of catheterization of the right side of the heart. Results were compared with the cardiac output and indexes of pulmonary arterial blood flow estimated with velocity-encoded magnetic resonance (MR) imaging. Correlations were good between estimates with right-sided heart catheterization and those with velocity-encoded MR imaging. By providing accurate pulmonary arterial blood flow measurements, velocity-encoded MR imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
77
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 27 publications
2
77
3
Order By: Relevance
“…First, as already mentioned (12), outlining is facilitated by the known proton inflow phenomenon, which enhances the blood signal within the vessel in MR imaging magnitude images. Therefore, the outlining method has limitations when the flow is weak, as in the enddiastolic part of the cardiac cycle, especially in the case of PAH (14). Moreover, it has been shown (l3) that physiological cardiac period variations, occurring during the phase-mapping acquisition, could disturb the recording of the end-diastolic cardiac phase.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, as already mentioned (12), outlining is facilitated by the known proton inflow phenomenon, which enhances the blood signal within the vessel in MR imaging magnitude images. Therefore, the outlining method has limitations when the flow is weak, as in the enddiastolic part of the cardiac cycle, especially in the case of PAH (14). Moreover, it has been shown (l3) that physiological cardiac period variations, occurring during the phase-mapping acquisition, could disturb the recording of the end-diastolic cardiac phase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated (7,14) that the systolic flow pattern is modified in the case of PAH. In the present series, analysis of the flow patterns over the complete cardiac cycle revealed that they were qualitatively different from those described in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a ventilation/perfusion (V/Q) lung scan is generally performed early in the diagnostic pathway to differentiate patients with CTEPH from those with other forms of pulmonary hypertension, selective digital subtraction angiography (DSA) combined with right heart catheterization is considered the gold standard for evaluating the disease and for assessment of treatment response and other concerns. However, it has been suggested that recent progress in noninvasive radiological methods such as cardiac echography (cardiac US), contrast-enhanced multidetector-row computed tomography (CE-MDCT) without and with electrocardiogram (ECG) triggering, and phase-contrast magnetic resonance imaging (MRI) have rendered these procedures useful for the above-mentioned purposes in routine clinical practice (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…With these techniques pulmonary circulation can be assessed both quantitatively and qualitatively, and they have shown moderate to good correlation with quantitative pulmonary circulation parameters assessed with cardiac US and/or right heart catheterization (4)(5)(6)(7)(18)(19)(20)(21). However, there have been no reports on the potential of quantitative and qualitative pulmonary perfusion parameters obtained from dynamic CE-perfusion MRI and time-resolved MRA images for assessment of therapeutic effects on CTEPH patients.…”
mentioning
confidence: 99%